Answer:
x=-4, x=10
Step-by-step explanation:
Hi there!
We want to solve this equation:
(x-3)²=49
We can move 49 to the other side, since the equation is to the second degree
(x-3)²-49=0
We now have a difference of squares equation (which is (a+b)(a-b)=a²-b²)
In this case, a² is (x-3)² and b² is 49
Taking the square root would result in that a is (x-3) and b is 7
So we can factor the equation as:
(x-3+7)(x-3-7)=0
Now combine like terms in between the two binomials
(x+4)(x-10)=0
Split and solve:
x+4=0
x=-4
x-10=0
x=10
So the answers are x=-4 and x=10
Hope this helps!